Pengaruh Konsentrasi Pupuk Organik Cair Bonggol Pisang terhadap Pertumbuhan dan Hasil Bunga Krisan (Chrysanthemum sp.) - Saragih, Laura Tantri Ervianta; Wijana, Gede; Astawa, I Nyoman Gede (Agrotrop : Journal on Agriculture Science; Vol 15 No 1 (2025), 2025)
Effect of Banana Weevil Liquid Organic Fertilizer Concentratio on the Growth and Yield of Flower Krisan ( Chrysanthemum sp.) . Chrysanthemum plants are one of the horticultural commodities that are in great demand by the public. Chrysanthemum plants are cultivated because their flowers and leaves have beauty and attractiveness in color, shape and type. One effort that can be made to increase the growth and yield of chrysanthemums is to provide liquid organic banana hump fertilizer. The aim of the research was to determine the effect of giving and finding the best concentration of banana hump liquid organic fertilizer on the growth and yield of chrysanthemum flowers. This research used a completely randomized design with one factor with 5 concentration treatments, namely 0 ml/l, 30 ml/l, 60 ml/l, 90 ml/l, 120 ml/l with 5 repetitions. The parameters observed were plant height, stem diameter, number of leaves, leaf area, age at flower emergence, number of flowers, weight of fresh flowers per pot, and leaf chlorophyll. The results of the research showed that the application of banana hump liquid organic fertilizer had a very significant effect on the growth and yield of chrysanthemums with 120 ml/? of water producing 11.47 flower heads, which was higher than without banana hump liquid organic fertilizer, which was 7.20 flower heads.